The dialectical questions : Erotemata dialectices - Melanchthon, Philipp (International studies in the history of rhetoric, 2021)
"The Dialectical Questions offers an English translation of the Erotemata Dialectices, the final and fullest textbook on the art of argumentation written by the reformer and educational innovator Philip Melanchthon (1497-1560). Representing an era when rhetoric and dialectic were seen as interdependent, companion arts, Melanchthon's textbook was widely used in Protestant Latin schools and universities during the Reformation. The translation tracks revisions to the text across its lifetime editions (1547-1560) and traces its classical sources. The introduction chronicles the personal and political upheavals that Melanchthon experienced during its composition, and provides an overview of its rich and complex content. It then focuses on the unique feature that sets this work apart from other early modern dialectics: its many sample arguments drawn from medicine and natural philosophy"--